Faktor - Faktor Yang Mempengaruhi Self Management Efek Samping Kemoterapi pada Pasien Kanker - Cahyono, Hendra Dwi; Martiana, Ina (Jurnal Ilmiah Kesehatan Rustida, 2024)
Cancer patients ecperiences various inpleasent symphtoms including fatigue, nausea and vomiting which could be included by the disease or its treatment which lead to poor adaptaition as result of inadequate self-management of chemotherapy side effect. This study was a cross sectional study with consecutive sampling. A total of 55 participants were join this study. Self management was assessed with questionnaire with reliability indekx of 0,75. Data analysis was done using chi square. The result shows a significant correlation between Self management to age (p value 0,027), gender (p value 0,012), management of fatigue (0,000), and management ofnausea and vomiting (p value 0,000). In conclusion, gender and educational level had significant influence on the respondent’s Self management ability. It was therefore, recommended that patients should be educated on strategies to manage post chemotherapy symptoms such as fatigue, nausea, and vomiting.